Analysis of Students’ Argumentation Skills in Socioscientific Issue-Based Electrochemistry Learning on Electric Vehicle Batteries - Mashami, Ratna Azizah (Journal of Authentic Research, 2026)
Scientific argumentation is essential for enabling students to evaluate evidence and make informed decisions about complex scientific and technological issues. This study aimed to describe chemistry education students’ argumentation skills in socioscientific issue-based electrochemistry learning using electric vehicle batteries as the context. A descriptive study using qualitative content analysis supported by descriptive statistics was employed. The participants were 15 undergraduate chemistry education students selected through saturated sampling. Data were collected through a five-item written argumentation test and semi-structured interviews with six students representing high, moderate, and low performance categories. Students’ responses were analyzed using Toulmin’s argumentation components: claim, data, warrant, backing, qualifier, and rebuttal. The results showed that students’ overall argumentation skills was moderate. Five students (33.3%) were classified in the high category, seven (46.7%) in the moderate category, and three (20.0%) in the low category. Claim was the strongest component, whereas rebuttal was the weakest. High-performing students were able to connect electrochemical concepts with battery production, degradation, recycling, and environmental impacts, while lower-performing students relied more heavily on general opinions and showed limited scientific justification. These findings indicate that socioscientific issue-based electrochemistry learning should provide more explicit support for developing warrants, qualifiers, and rebuttals.